PENGARUH KOMITMEN ORGANISASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA (STUDI KASUS PADA GURU SMA KESATRIAN DALAM YAYASAN PENDIDIKAN KESATRIAN - ., Sunarno; Liana, Lie (Proceeding SENDI_U, 2015)
The results of this study are the Influence of organizational commitment, organizational culture and jobsatisfaction on teacher performance. The research problems in this study are: (1) to examine the influence oforganizational commitment, school culture, and job satisfaction on teacher performance. (2) to test whether jobsatisfaction mediates organizational commitment, school culture of the teacher performance. The samples ofthis study are 103 teachers of Kesatrian Senior High School under the Kesatrian Education Foundation inSemarang. The used sampling was census techniques and the used model was multiple regression analysis. Theresults of this study are: (1) organizational commitment is not proved in influencing the job satisfaction, (2)school culture has positive and significant influence on the job satisfaction, (3) organizational commitment wasnot proved in influence on teacher performance, (4) school culture has positive and significant influence onteacher performance, (5) the job satisfaction has positive and significant influence on teacher performance, (6)job satisfaction variable is not proved having the function as intervening variable on the variable of schoolculture on teacher performance.Keywords: organizational commitment, school culture, job satisfaction, teacher performance.